Reconstruction of post-war ruined cities through tourism development case study: Khorram-Shahr, Iran / Seyed Mehdi Mirisaee - Seyed Mehdi, Mirisaee (2017)
Reconstruction of post-war ruined cities is one of the most important objectives for the public and governments, because the ultimate goal is to repatriate immigrants and to establish an ordinary life for new and former residents after the conflict. Communities that have experienced urban restoration in the past decade chose the tourism sector as a potential source of revenue, which subsequently contributes to urban reconstruction. Nonetheless, the potential of tourism development in the post-war reconstruction has been minimally investigated by researchers. Thus, the question on how to use post-war tourism potential to reconstruct ruined cities after war remains unclear. This study focuses on tourism strategies in the reconstruction of the post-war city of Khorramshahr, Iran, which had significant urban destructions and the social changes to the city after eight years of conflict although had the prosperous background in tourism. Aspects of the research were on tourism strategies in the reconstruction of the post-war city based on the four main concepts that were derived from the literature review: government policy, architecture, urban fabric, and infrastructure. The sequential mixed method (qualitative and quantitative) was adopted to carry out this study. The findings of this study highlighted: firstly, the important evidences to support the need to review the current tourism policy in Khorramshahr to build support of residents and to improve the flow of tourism benefits to them. Secondly, the Jame Mosque area and the river banks as post-war tourism have been the most relevant tourist attraction criteria in Khorramshahr. Based on the above findings, this study offered some suggestions that: (a) the government roles should be revised to provide opportunities for the private sector and resident of Khorramshahr; (b) the attractions of new development that can work with the leisure tourism should be identified; and (c) the harbour plays an important role and its significance in the reconstruction process should be given due consideration. Significantly, this study provided the valuable reference materials to urban policy-makers, designers, architects, and tourism stakeholders from the study outcomes with regard to development of post-war tourism.